The Late Capitanian Mass Extinction of Terrestrial Vertebrates in the Karoo Basin of South Africa - Day, Michael O.; Rubidge, Bruce S. (Frontiers in Earth Science, 2021)
The Beaufort Group of the main Karoo Basin records two major extinction events of terrestrial vertebrates in the late Palaeozoic. The oldest of these has been dated to the late Capitanian and is characterized by the extinction of dinocephalian therapsids and bradysaurian pareiasaurs near the top of Tapinocephalus Assemblage Zone. Faunal turnover associated with the extinction of dinocephalians is evident in vertebrate faunas from elsewhere in Pangaea but it can be best studied in the Karoo Basin, where exposures of the upper Abrahamskraal and lower Teekloof formations allow continuous sampling across the whole extinction interval. Here we present field data for several sections spanning the Capitanian extinction interval in the southwestern Karoo and discuss recent work to establish its timing, severity, and causes. A large collections database informed by fieldwork has demonstrated an increase in extinction rates associated with ecological instability that approach that of the end-Permian mass extinction, and shows significant turnover followed by a period of low diversity. Extinctions and recovery appear phased and show similarities to diversity patterns reported for the Permo-Triassic mass extinction higher in the Karoo sequence. The mass extinction of terrestrial vertebrates in the Karoo coincides with volcanism in the Emeishan Large Igneous Province and may have been partly driven by short-term aridification, but clear causal mechanisms and robust links to global environmental phenomena remain elusive.